The Next Could Be Me - Ali, Ahila (Journal of Pakistan Psychiatric Society, 2026)
This essay reflects the dual reality of being a female medical student in Pakistan, where hope and fear coexist. It highlights the aspiration to become a successful doctor while confronting societal pressures, gender-based violence, and systemic barriers. Through a deeply personal narrative, the essay challenges stigma, emphasizes mental resilience, and calls for empathy and change. By shifting the perspective from distant victims to personal vulnerability, it reinforces a powerful message: mental health struggles and societal injustices can affect anyone; the next could be me.